THE INFLUENCE OF NANOCOMPOSITE FILLER ON THE LIFETIME PERFORMANCE OF POLYPROPYLENE UNDER VOLTAGE POLARITY REVERSAL - Setiawan, Achmad
Many researchers are giving more attention to study the field of the dielectric and electrical insulation of nanocomposite materials. To understand basic electrical properties of nanocomposite polypropylene, this work investigates the influence of nanostructuring on DC breakdown strength, life under periodic voltage polarity reversals and space charge accumulation properties. Results show that unfilled samples feature higher charge accumulation, lower breakdown strength, and shorter life than the nanocomposite counterpart. Based on these results, it is clear that nanostructured dielectrics can give an important improvement in electrical insulation properties.